THE EFFECTIVENESS OF USING GAME TECHNOLOGIES IN IN-DEPTH TEACHING OF ENGLISH LESSONS FOR PRIMARY SCHOOL STUDENTS - Maxmudova Nilufar, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines the effectiveness of using game technologies in English lessons for primary school students. Games provide opportunities to increase students' motivation, make the lesson process interesting, develop social skills, and apply the language practically. The article presents the advantages and various examples of using game technologies, which will help teachers conduct lessons more effectively. Game technologies play an important role in making the process of learning English interesting and interactive.